Measuring Indonesian EFL Learners’ English Vocabulary Knowledge: A Rasch Analysis Approach - Dairabi Kamil (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2021)
This study sought to, first, measure Indonesian EFL learners’ vocabulary knowledge across four modalities, i.e. Active Recall, Passive Recall, Active Recognition, and Passive Recognition; second, determine whether or not there were statistically significant differences between male and female participants’ vocabulary knowledge and third, determine whether or not the participants’ vocabulary knowledge across the four modalities were correlated. Data were collected by administering four sets of vocabulary tests to 71 EFL learners at an English Department of a higher education institution in Indonesia. Data were analyzed using Rasch analysis and Spearman's-Rho correlation technique. The results showed that the participants performed better on the recognition tests than on recall tests. No statistically significant difference was found between male female participants’ vocabulary knowledge. Moderate and strong correlations were found among the participants’ Passive Recall and Active Recognition, Passive Recall and Passive Recognition, and Active Recognition and Passive Recognition.